122 million more people pushed into hunger since 2019 due to multiple crises, reveals UN report - World Health Organization (World Health Organization, 2023)
Over 122 million more people are facing hunger in the world since 2019 due to the pandemic and repeated weather shocks and conflicts, including the war in Ukraine, according to the latest State of Food Security and Nutrition in the World (SOFI) report published today jointly by five United Nations specialized agencies.
Keywords: 2023-07 July; Food Security and Nutrition